Biannual research and Innovation Bulletin - Machakos University (Machakos University Press, 2019)
Continuing with our nonthemed issues, we are pleased to present our second issue of the series of Machakos University Biannual Research and Innovation Bulletin. The Editorial Board has again assembled a diverse group of articles that provide something of interest to our varied readership. We would like to thank the University Management and the entire Machakos University fraternity for support towards enhancing research, innovation and technology transfer. This publication covers a wide range of research, innovation and technology transfer including but not limited to funded research and development programs, scholarly publications, dissemination of research findings and community engagements and innovations. We extend our appreciation for all your efforts and achievements and best wishes to you for your generous support as we pursue our University mission.We hope that you enjoy reading the newsletter and that the ideas can help to shape the current dialogue and strengthen our research and innovation agenda. On behalf of the Editorial Board, I would like to thank our contributors for their efforts and hope our readers continue to find useful and interesting information in this Second Issue